A continuum manipulator for continuously variable stiffness and its stiffness control formulation. (July 2020) - Zhao, Bin; Zeng, Lingyun; Wu, Zhonghao; Xu, Kai
Highlight: A 2-segment continuum manipulator is designed for adjustable stiffness. Multi-backbone placement and constrained bending curvature varies the stiffness. Cosserat rod theory is applied in the kinestatic model. A stiffness control formulation is proposed for tip stiffness control. The experiments show effectiveness of the proposed idea. Abstract: Continuum manipulators can accomplish tasks in cluttered and unstructured environments due to their slenderness. Balancing the workspace and stiffness of the slender continuum manipulator is a primary design concern. Thus, studies have been consistently dedicated to designing continuum manipulators with high or variable stiffness. This paper proposes a 2-segment continuum manipulator with adjustable stiffness based on continuously constrained bending curvature. The manipulator's stiffness is further enhanced via redundant backbone arrangement using the concept of dual continuum mechanism during the design phase. The Cosserat rod theory is used for the kinestatic model to calculate the tip stiffness of the manipulator. A stiffness control formulation utilizes the configuration redundancy of the manipulator to achieve stiffness variation control in a desired direction at a target position. The design concepts, system construction, kinestatic models, stiffness control formulation and experimental validations are presented. The experimental results showed that the tip stiffness of the manipulator can be adjusted in various directions with an enhancement up to 10.83 times of the minimal stiffness, indicating the efficacy of the proposed design and the stiffness control formulation.